Analisis Peranan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah di Kota Banjarmasin - Rahmat, Baihaqqi; Yunani , Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study discusses the analysis of the role of street lighting tax on local revenue in Banjarmasin. In administering the Street Lighting Tax (PPJ), the Government, through the Regional Revenue Service, oversees implementing the Street Lighting Tax (PPJ). Still, in the case of managing its tax collection, the Regional Revenue Service cooperates with PLN in collecting street lighting taxes. This research is conducted with a quantitative descriptive analysis method to calculate growth rate, effectiveness, and contribution. The method used in this study is through the growth rate of road lighting taxes and the effectiveness of street lighting. For street lighting tax, the highest growth rate in 2014 was 19.62%, the lowest growth rate was in 2016 at 1.7%, while for the last year of 2018, the growth rate was 12.82%, from the calculation of the growth rate indicator ≤ 30% is still considered unsuccessful, and the average total calculation is 11.71%.